Deciphering the Trophic Ecology of Three Marlin Species Using Stable Isotope Analysis in Temperate Waters Off Southeastern Australia - Guillemin, Tristan A.; Pepperell, Julian G.; Gaston, Troy; Williamson, Jane E. (Frontiers in Marine Science, 2022)
Understanding the unique feeding behaviours of oceanic fish, such as marlin, is key to their effective management. Marlin are notoriously difficult to study, however, and the limited research on marlin feeding shows that diet can vary greatly between species and geographic regions. One region where marlin feeding behaviours are particularly poorly understood are temperate eastern Australian waters. This study collected marlin tissue from game fishing tournaments between latitudes 32°43′06.5″S/152°08′50.1″E to 34°40′12.9″S/150°51′34.3″E between 2010 and 2021, and used stable isotope analysis (SIA) to assess the trophic ecology of the three species of marlin occurring in the region: black (Istiompax indica), blue (Makaira nigricans), and striped (Kajikia audax) marlin. All species had similar δ13C values, but δ15N differed between species, with higher variability observed in blue marlin than in the other two species. Sulphur isotopes were key in identifying the relative contribution of coastal or benthic influences on marlin diet, with δ34S suggesting that blue marlin had less coastal/benthic dietary influence than black or striped marlin. Incorporation of δ34S into SIA for marlin is thus recommended for future studies. Some differences in isotope values across locations and dates were found, however, the uneven sample sizes due to the opportunistic sampling limited the ability to understand spatial or seasonal differences. These findings show that marlin followed similar dietary trends to conspecifics in other regions despite temperate eastern Australian waters being one of the few with three marlin species commonly co-occuring. This suggests that interspecies resource competition is not a major force driving the demography of these species in eastern Australian waters. This research highlights a need for specific management strategies at a species level, particularly for blue marlin. Future research incorporating prey isoscapes and baselines assessed over a wider range of marlin sizes is suggested to further improve our knowledge and capacity to manage the marlin of eastern Australian waters.